2013
DOI: 10.1097/01.ogx.0000435526.35453.45
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Adipokine Levels and Endometrial Cancer Risk in the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial

Abstract: Background-Circulating adipokine levels may be associated with endometrial cancer risk, yet few studies have evaluated these markers prospectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
52
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(60 citation statements)
references
References 32 publications
5
52
3
Order By: Relevance
“…37,38 For conducting the dose-response meta-analysis, the following information were needed: (i) the distribution of cases and noncases and the risk estimates with the variance estimates for at least three quantitative exposure categories; (2) the median or mean level of these exposures in each category (if reported by ranges, mean level was calculated by averaging the lower and upper bound; if the lowest category was open ended, the lowest boundary was considered to be zero; if the highest category was open ended, the open-ended interval length was assumed to be the same as the adjacent interval). Given this, eight studies 16,19,20,[22][23][24][25]27 met the criteria and were included in the dose-response analysis of circulating adiponectin concentrations and endometrial cancer risk. However, limited by the number of studies met those criteria, 16,19,24 we failed to carry out the dose-response analysis of leptin and A/L ratio.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…37,38 For conducting the dose-response meta-analysis, the following information were needed: (i) the distribution of cases and noncases and the risk estimates with the variance estimates for at least three quantitative exposure categories; (2) the median or mean level of these exposures in each category (if reported by ranges, mean level was calculated by averaging the lower and upper bound; if the lowest category was open ended, the lowest boundary was considered to be zero; if the highest category was open ended, the open-ended interval length was assumed to be the same as the adjacent interval). Given this, eight studies 16,19,20,[22][23][24][25]27 met the criteria and were included in the dose-response analysis of circulating adiponectin concentrations and endometrial cancer risk. However, limited by the number of studies met those criteria, 16,19,24 we failed to carry out the dose-response analysis of leptin and A/L ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Given this, eight studies 16,19,20,[22][23][24][25]27 met the criteria and were included in the dose-response analysis of circulating adiponectin concentrations and endometrial cancer risk. However, limited by the number of studies met those criteria, 16,19,24 we failed to carry out the dose-response analysis of leptin and A/L ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMI: body mass index. 5 Recent BMI models not adjusted for recent BMI. 6 Wald test for interaction between body size and postmenopausal hormone use (examined in base multivariate model).…”
Section: Epidemiologymentioning
confidence: 99%
“…(14) Additionally, epidemiological studies found that lower serum adiponectin levels were linked with an increased incidence of cancers of the colon, breast, and endometrium. (15)(16)(17) Several SNPs in the gene encoding adiponectin (ADIPOQ) were associated with increased prostate cancer risk in Caucasians, (18) of which rs266729 was previously shown to be associated with an enhanced risk of lung, colon, and breast cancers. (19)(20)(21)(22) Recently, genetic variants of rs266729 and rs182052 SNPs were found to be associated not only with prostate cancer risk but also with different circulating adiponectin levels.…”
mentioning
confidence: 99%